A concepção de integração da América Latina presente nas práticas educativas da Escola Latino Americana de Agroecologia - Legnani, Andréa Marcia (2014)
This study addresses the theme on the Latin America integration from the Latin American School of Agroecology (ELAA) perspective. It deals with a central category of study the Integration of Latin America and Social Movements in order to understand and analyze the design of Latin American integration in the educational practices of ELAA. The debates on Latin America integration are focused on economic aspects; the study is aimed at presenting an idea of what would be the economic integration, as it is important to present a concept based on the integration of people. The first chapter, "Integration of Latin America: Concepts, History, Treaties and Agreements", establishes a theoretical plan that provides an understanding of the subject matter, making a historical review of the Latin America idea, as well as the idea of its integration, raising the debate on integration versus fragmentation, thus seeking to provide a summary of the main integrationist projects implemented in Latin America since 1960. In the second chapter, "The Social Movements Category and the Integration of Latin America", our goal is to work the Social Movements category by introducing a concept seen as a Social Movement, bringing a little of the trajectory of social movements in Latin America, describing and analyzing Latin American integration, specially under through the prism of MST (Landless Workers' Movement), correlated to their educational principles. The third chapter, "The Conception of the Latin America Integration from the Latin American School of Agroecology (ELAA) perspective", presents ELAA and its dynamics, connected to the description, understanding and analysis of the concept of Latin America integration from the School perspective, and seeking to apprehend, in their educational practices, how such theme works. The concept of Latin America integration to ELAA in their educational practices is the integration between the peoples, provided by the exchange of knowledge and experiences, with preservation of cultures and the sovereignty of countries, as education plays a key role in contributing to such integration.